Intrafamilial variability in six family members with ERF‐related craniosynostosis syndrome type 4. Issue 10 (19th July 2022) - Moddemann, Marina K.; Kieslich, Matthias; Koenig, Rainer
Abstract: ERF ‐related craniosynostosis syndrome type 4 (CRS4, OMIM #600775) is a rare autosomal dominant malformation syndrome, caused by pathogenic variants in the ERF gene and characterized by craniosynostosis, developmental delay, and dysmorphic features such as hypertelorism, exophthalmos, depressed nasal bridge, and retrognathia. So far, there are mostly individual reports and only a few descriptions of families with more than two affected patients, allowing statements about the penetrance of a certain variant and its variability only to a limited extent. In this study, we report an in‐depth analysis of the clinical course of six family members from three generations with the novel heterozygous nonsense variant c.286A>T (p.Lys96*) in the ERF gene. At the time of examination, all of the six patients showed mild dysmorphic features and brachydactyly, five were overweight/obese and had delayed speech development, and four were short in stature. Hyperactivity, a short concentration span and a history of learning difficulties were found in half of the affected family members. To this day, none of the patients developed increased intracranial hypertension that would require surgical intervention. This work provides further information on the expressive variability of an ERF variant in six members of one family and focuses on the need for close neuropediatric surveillance.